Rare variants in the sodium-dependent phosphate transporter gene SLC34A3 explain missing heritability of urinary stone disease - Sadeghi-Alavijeh, O; Chan, MMY; Moochhala, SH; Howles, SA; Gale, DP; Böckenhauer, D (Elsevier, 2023)
Urinary stone disease (USD) is a major health burden affecting over 10% of the United Kingdom population. While stone disease is associated with lifestyle, genetic factors also strongly contribute. Common genetic variants at multiple loci from genome-wide association studies account for 5% of the estimated 45% heritability of the disorder. Here, we investigated the extent to which rare genetic variation contributes to the unexplained heritability of USD. Among participants of the United Kingdom 100,000-genome project, 374 unrelated individuals were identified and assigned diagnostic codes indicative of USD. Whole genome gene-based rare variant testing and polygenic risk scoring against a control population of 24,930 ancestry-matched controls was performed. We observed (and replicated in an independent dataset) exome-wide significant enrichment of monoallelic rare, predicted damaging variants in the SLC34A3 gene for a sodium-dependent phosphate transporter that were present in 5% cases compared with 1.6% of controls. This gene was previously associated with autosomal recessive disease. The effect on USD risk of having a qualifying SLC34A3 variant was greater than that of a standard deviation increase in polygenic risk derived from GWAS. Addition of the rare qualifying variants in SLC34A3 to a linear model including polygenic score increased the liability-adjusted heritability from 5.1% to 14.2% in the discovery cohort. We conclude that rare variants in SLC34A3 represent an important genetic risk factor for USD, with effect size intermediate between the fully penetrant rare variants linked with Mendelian disorders and common variants associated with USD. Thus, our findings explain some of the heritability unexplained by prior common variant genome-wide association studies.